Intravenous contrast material administration in multislice computed tomography coronary angiography - Cademartiri, F.; Luccichenti, G.; Gualerzi, et al., M. (Acta Biomedica Atenei Parmensis, 2005)
Rationale and objectives: to compare contrast material (CM) administration protocols in non-invasive coronary angiography (CA) using a 16-row multislice CT (16-MSCT). Methods: 45 patients undergoing CA with 16-MSCT were divided into three CM protocols: group 1 (140 ml@4ml/s), group 2 (140 ml = 60 ml@5ml/s + 80 ml@3ml/s), and group 3 (100 ml@4ml/s). The attenuation at the origin of the coronary vessels was assessed. Three regions of interest were evaluated: 1) ascending aorta (ROI1); 2) descending aorta (ROI2); 3) pulmonary artery (ROI3). The resulting time-density curves generated the average attenuation and the slope of bolus geometry. Results: the attenuation at the origin of the coronary vessels, and the average attenuation of bolus geometry were not significantly different (p>0.05). The slope of bolus geometry was in ROI1 and ROI2 significantly lower for group 2, in ROI3 significantly lower for group 3 (p<0.05). Conclusion: 100 ml of CM provide the same attenuation in 16-MSCT CA as mono- or multi-phasic 140 ml protocols.